K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 8 2023

\(4x\left(2x-5\right)+x\left(3-x\right)=0\)

\(\Rightarrow8x^2-20x+3x-x^2=0\)

\(\Rightarrow7x^2-17x=0\)

\(\Rightarrow x\left(7x-17\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x=0\\7x=17\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{17}{7}\end{matrix}\right.\)

26 tháng 2 2023

`a)` P(x)= 2x³ + x² +5 -3x + 3x²- 2x³ - 4x² + 1

`P(x) = (2x^3 -2x^3) + (x^2 +3x^2 -4x^2)-3x +(1+5)`

`P(x) = -3x +6`

Vậy `P(x) = -3x +6`

b) cho `P(x) = 0`

`<=> -3x+6 =0`

`-3x =-6`

`=> x =2`

cho P(x) =1

`=> -3x +6 =1`

`<=> -3x =-5`

`x =5/3`

a: \(P\left(x\right)=5x^5-4x^4-2x^3+4x^2+3x+6\)

Bậc là 5

\(Q\left(x\right)=-5x^5+4x^4+2x^3-4x^2+7x+\dfrac{1}{4}\)

Bậc là 5

b: H(x)=P(x)+Q(x)

\(=5x^5-4x^4-2x^3+4x^2+3x+6-5x^5+4x^4+2x^3-4x^2+7x+\dfrac{1}{4}\)

=10x+6,25

c: Để H(x)=0 thì 10x+6,25=0

hay x=-0,625

17 tháng 6 2019

Bài 1 ( a )

\(A_x=-4x^5-x^3+4x^2+5x+9+4x^5-6x^2-2\)

\(=-x^3-2x^2+5x-7\)

\(B_x=-3x^4-2x^3+10x^2-8x+5x^3-7-2x^3+8x\)

\(=-3x^4+x^3+10x^2-7\)

17 tháng 6 2019

Bài 1 ( b )

\(P_x=\left(-x^3-2x^2+5x-7\right)+\left(3x^4+x^3+10x-7\right)\)

\(=-x^3-2x^2+5x-7+3x^4+x^3+10x-7\)

\(=3x^4-2x^2+15x-14\)

\(Q_x=\left(-x^3-2x^2+5x-7\right)-\left(3x^4+x^3+10x-7\right)\)

\(=-x^3-2x^2+5x-7-3x^4-x^3-10x+7\)

\(=-3x^4-2x^3-5x\)